A novel method for determination of inorganic polyphosphates using the fluorescent dye fura-2 - Lorenz, B. (2015)
A method for determining inorganic polyphosphate, which is based on the Mn2+-induced quenching of the fluorescence of the calcium indicator fura-2, is described. The effect of Mn2+ ions on fura-2 fluorescence is gradually abolished in the presence of increasing concentrations of polyphosphate; this allows the quantification both of synthetic polyphosphates and of the naturally occurring polymer isolated from tissues or cells. The described method has some advantages compared to conventional procedures for detection of polyphosphates based on the metachromatic effect on toluidine blue. It can be applied for the determination of pyrophosphate, tripolyphosphate and other short-chain polyphosphates not detectable by toluidine blue and it can be used for measurement both of pyrophosphatase and exopolyphosphatase activity. (C) 1997 Academic Press.